2018
DOI: 10.21608/ajfm.2018.15875
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Triage Vital Signs and Conscious Level for Outcome Evaluation in Acutely Organophosphate Poisoned Patients

Abstract: Triage in Emergency departments requires emergency doctors to make rapid decisions based on their knowledge and experiences. Triage of patients is critical to patient safety, yet no clear information exists by the utility of initial vital signs and conscious level in identifying critically ill acutely organophosphate (OP) poisoned patients. The objective of this study is to determine the relationship between triage vital signs and conscious level in predicting outcome of acutely organophosphate poisoned patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…LCGA in our study indicated that the highremitting trajectory of respiratory rate was linked to mortality. However, these results were in contrast with previous studies, as high temperature and low respiratory rate have exhibited significance with mortality in multiple studies [26,47,49,50], though nonsignificance for respiratory rate [47] and temperature [48] was observed in a study of OP poisoning patients. Multiple studies have investigated vital signs but not PO 2 [47,50,51], whereas our study showed that a normal-remitting partial oxygen pressure trajectory is linked to an increased risk of mortality.…”
Section: Summary Of Findingscontrasting
confidence: 99%
“…LCGA in our study indicated that the highremitting trajectory of respiratory rate was linked to mortality. However, these results were in contrast with previous studies, as high temperature and low respiratory rate have exhibited significance with mortality in multiple studies [26,47,49,50], though nonsignificance for respiratory rate [47] and temperature [48] was observed in a study of OP poisoning patients. Multiple studies have investigated vital signs but not PO 2 [47,50,51], whereas our study showed that a normal-remitting partial oxygen pressure trajectory is linked to an increased risk of mortality.…”
Section: Summary Of Findingscontrasting
confidence: 99%
“…Regarding respiratory rate, abnormalities were recorded in 27.6 % of patients (20.7% had tachypnea, 6.9% with bradypnea). Other studies as Banerjee et al, (2012) and Moussa et al, (2018) reported that tachypnea represented 6%, 35% of cases respectively. Tachypnea may be a sign of respiratory failure (Sungur and Güven, 2001).…”
Section: Resultsmentioning
confidence: 82%
“…This is explained by Rabha et al, (2017) as preganglionic nicotinic receptor stimulation was followed by release of adrenaline and noradrenaline from adrenal gland leading to predominance of adrenergic activity on the heart. Moussa et al, (2018) found that 9.5% of patients presented with tachycardia and 1.5% of patients presented with bradycardia. Concerning the blood pressure, they found 5% of their patients had hypotension, 2% of patients had hypertension.…”
Section: Resultsmentioning
confidence: 96%
“…The mortality rate in the Amin et al ( 2018) study was 11.53%. Also, Moussa et al (2018) study reported mortality rate by 10 %. Furthermore, Abdel Baseer et al (2021) reported that mortality rate was 5.5%.…”
Section: Discussionmentioning
confidence: 94%